2022
DOI: 10.3390/jof8060562
|View full text |Cite
|
Sign up to set email alerts
|

Neopestalotiopsis siciliana sp. nov. and N. rosae Causing Stem Lesion and Dieback on Avocado Plants in Italy

Abstract: Avocado (Persea americana) represents an important emerging tropical crop in Italy, especially in the southern regions. In this study, young plants of avocado showing symptoms of stem and wood lesion, and dieback, were investigated. Isolations from symptomatic tissues consistently yielded colonies of Neopestalotiopsis-like species. The characterization of representative isolates was based on the observation of morphological characters, the effect of temperature on mycelial growth rate, and on the sequencing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 69 publications
2
16
0
Order By: Relevance
“…After that, the number of species in Neopestalotiopsis increased from 24 to 73, and the number of species in Pseudopestalotiopsis increased from 3 to 23 ( http://www.indexfungorum.org/ , 10 Nov 2022). In recent years, there have been more reports on diseases caused by Neopestalotiopsis ; for example, N. vitis caused grapevine leaf spots in China, N. rosicola caused stem canker of Rosa chinensis in China, N. clavispora caused leaf spots and fruit rot of strawberry in India, N. maddoxii caused flower diseases of Macadamia integrifolia in Australia, N. eucalyptorum was associated with disease of Eucalyptus plants in Portugal, and N. siciliana caused stem lesion and dieback on avocado plants in Italy ( 22 , 23 , 26 , 29 , 30 , 63 ). However, only six Pseudopestalotiopsis species were reported as plant pathogens ( 47 , 64 67 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After that, the number of species in Neopestalotiopsis increased from 24 to 73, and the number of species in Pseudopestalotiopsis increased from 3 to 23 ( http://www.indexfungorum.org/ , 10 Nov 2022). In recent years, there have been more reports on diseases caused by Neopestalotiopsis ; for example, N. vitis caused grapevine leaf spots in China, N. rosicola caused stem canker of Rosa chinensis in China, N. clavispora caused leaf spots and fruit rot of strawberry in India, N. maddoxii caused flower diseases of Macadamia integrifolia in Australia, N. eucalyptorum was associated with disease of Eucalyptus plants in Portugal, and N. siciliana caused stem lesion and dieback on avocado plants in Italy ( 22 , 23 , 26 , 29 , 30 , 63 ). However, only six Pseudopestalotiopsis species were reported as plant pathogens ( 47 , 64 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…The sequences were compared against the NCBI GenBank nucleotide database using BLASTn to evaluate the closest phylogenetic matches. All sequences used in this study were downloaded from GenBank referring to previous studies ( 16 , 23 , 27 , 30 , 44 , 65 , 67 , 76 79 ) ( Table 3 ). The single-gene sequences were checked with BioEdit v. 7.0.9.0 ( 80 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Newly-generated sequence data in this study were observed and manually adjusted via BioEdit version 7.2.5 ( Hall et al 2011 ; http://bioedit.software.informer.com/ ) to check the quality of the sequences. Additional related sequences of pestalotiopsis-like fungi were downloaded from GenBank ( https://www.ncbi.nlm.nih.gov/nuccore ) based on recent publications ( Solarte et al 2018 ; Fiorenza et al 2022 ; Jiang et al 2022a , 2022b ; Peng et al 2022 ; Tian et al 2022 ; Xiong et al 2022 ; Zhang et al 2022 ; Guterres et al 2023 ; Sun et al 2023 ) and are listed in Suppl. material 1 : tables S2, S3.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The isolate was further identified by a phylogenetic tree with sequences of ITS (MH209245), TEF 1-α (MH460870), LSU (MH478108), TUB (MH460873) genes/regions. The analysis delineated it as Neopestalotiopsis guajavicola (Haq et al, 2021;Fiorenza et al, 2022). The pathogenicity test was conducted on twoyear-old P. guajava healthy plants, grown in earthen pots under natural conditions.…”
mentioning
confidence: 99%